Obesity Induces Hypothalamic Endoplasmic Reticulum Stress and Impairs Proopiomelanocortin (POMC) Post-translational Processing - Cakir, Isin (2013)
It was shown previously that abnormal prohormone processing or inactive proconverting enzymes that are responsible for this processing cause profound obesity. Our laboratory demonstrated earlier that in the diet-induced obesity (DIO) state, the appetite-suppressing neuropeptide -melanocyte-stimulating hormone ( -MSH) is reduced, yet the mRNA of its precursor protein proopiomelanocortin (POMC) remained unaltered. It was also shown that the DIO condition promotes the development of endoplasmic reticulum (ER) stress and leptin resistance. In the current study, using an in vivo model combined with in vitro experiments, we demonstrate that obesity-induced ER stress obstructs the post-translational processing of POMC by decreasing proconverting enzyme 2, which catalyzes the conversion of adrenocorticotropin to -MSH, thereby decreasing -MSH peptide production. This novel mechanism of ER stress affecting POMC processing in DIO highlights the importance of ER stress in regulating central energy balance in obesity.